2017
DOI: 10.1038/nchembio.2334
|View full text |Cite
|
Sign up to set email alerts
|

In silico design of novel probes for the atypical opioid receptor MRGPRX2

Abstract: The primate-exclusive MRGPRX2 G protein-coupled receptor (GPCR) has been suggested to modulate pain and itch. Despite putative peptide and small molecule MRGPRX2 agonists, selective nanomolar potency probes have not yet been reported. To identify a MRGPRX2 probe, we first screened 5,695 small molecules and found many opioid compounds activated MRGPRX2, including (−)- and (+)-morphine, hydrocodone, sinomenine, dextromethorphan and the prodynorphin-derived peptides, dynorphin A, dynorphin B, and α- and β-neoendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
263
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(273 citation statements)
references
References 60 publications
10
263
0
Order By: Relevance
“…A similar screen has suggested that the oGPCR MRGPRX2 is an atypical opioid receptor, responding to drugs like morphine, codeine, and dextromethorphan, as well as to the endogenous opioid peptide dynorphin 44 . MRGPRX2 is expressed in mast cells and sensory neurons, consistent with its role as an opioid itch receptor.…”
Section: New Chemistry For New Targetsmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar screen has suggested that the oGPCR MRGPRX2 is an atypical opioid receptor, responding to drugs like morphine, codeine, and dextromethorphan, as well as to the endogenous opioid peptide dynorphin 44 . MRGPRX2 is expressed in mast cells and sensory neurons, consistent with its role as an opioid itch receptor.…”
Section: New Chemistry For New Targetsmentioning
confidence: 98%
“…In our own lab, the platform has been used to screen for ligands that illuminate the function of orphan and understudied GPCRs (oGPCRs) 40 , such as MRGPRX2 (ref. 44). …”
Section: Allostery and Biasmentioning
confidence: 99%
“…One GPR68 PAM, ogerin, was demonstrated to have on-target activity in vivo by modulating conditioned fear responses in mice. A similar approach has recently been used to identify small molecule ligands for the oGPCRs GPR171 (Wardman et al, 2016) and MRGPRX2 (Lansu et al, 2017), and these compounds were subsequently used to further characterize the receptor’s role in feeding behavior and itch, respectively.…”
Section: Exploiting Gpcr-ligand Structures For Drug Discoverymentioning
confidence: 99%
“…Mast cells play a critical role in the host defence, and they are tissue‐resident multifunctional immune cells best known for their roles in allergic and inflammatory diseases . MRGPRX2 is a novel GPCR for the neuropeptide SP, antimicrobial host defence peptides (HDPs), FDA‐approved cationic drugs, and opioids, and is expressed at high levels in the human skin (MC TC ) . LAD2 cells are skin‐derived mast cells that express high levels of MRGPRX2 .…”
Section: Discussionmentioning
confidence: 99%